A review on IoT-based healthcare monitoring systems for patient in remote environments - Mohammed Al-Khazraji, Ali Abdul-Jabbar; Mohd Aboobaider, Burhanuddin; Talib, Mohammed Saad; Hameed, Mustafa Emad; Ali, Mohanad Faeq (Ubiquity Press, 2020)
The Internet of Things (IoT) is a powerful technology that can enable users’ smart devices and sensors to link each other and access the internet for daily usage. It is a platform that can be used by end users to access many smart application fields, such as smart city, smart home, and smart healthcare. In recent years, the healthcare monitoring systems are becoming the major development field that use the IoT as advanced technology enabler. This review is discussing more about the design, functions, and the main uses of the IoT-based healthcare monitoring applications and systems for remote patient environments. Therefore, a deep review has been made to identify the usage, efficiency, and acceptability for the current applications and systems to become more efficient to patients. Different healthcare monitoring systems have employed the IoT to integrate the different wireless interfaces with the cloud-based healthcare services. These services are including the sensing, gathering, processing, storing, and learning more among the patients’ data. The various IoT healthcare applications will help to develop useful and effective solutions by using these systems in practice. From this review it can be proof that the IoT-based healthcare monitoring applications are growing faster to build more healthcare solutions that useful for different healthcare conditions and environments.